Madurastatin B3, a rare aziridine derivative from actinomycete Nocardiopsis sp. LS150010 with potent anti-tuberculosis activity. (1st May 2017) - Zhang, Xinjun; He, Hongtao; Ma, Rong; Ji, Zengchun; Wei, Qi; Dai, Huanqin; Zhang, Lixin; Song, Fuhang
Abstract: Since the discovery of the first antibiotic, natural products have played an important role in chemistry, biology and medicine. To explore the potential of bioactive compounds from microbes isolated from the southeast of Tibet, China, a crude extract library was constructed and screened against Staphylococcus aureus . The strain Nocardiopsis sp. LS150010 was scaled up and subjected to further chemical studies, resulting in the identification of N -salicyloyl-2-aminopropan-1, 3-diol (2 ) and its rare aziridine derivative, madurastatin B3 (1 ). Their structures were determined by detailed analysis of 1D, 2D NMR and HRMS data. Compounds 1 and 2 displayed significant inhibitory activity against S. aureus and methicillin resistant S. aureus, with MIC values of 6.25 µg/mL. Compound 1 also showed potent inhibitory activity against Bacillus subtilis and Escherichia coli, as well as activity in a Mycobacterium tuberculosis Bacillus Calmette-Guérin infected THP-1 cell model.